Design and fabrication of foldable house stairs / Muhammad Al Ikram Akmal - Akmal, Muhammad Al Ikram (2022)
A folding staircase can be used to save space especially for a small house, or garage. It folds out of the way when not in use, as the name implies, making it the ideal alternative when you don't have enough space to install normal steps [1]. Stairs are one of architecture's oldest and most complex design problems. Aesthetics, pedestrian circulation, construction, and safety all work together to form a complex network of variables. Despite the fact that stairs are essentially parametric, designers have been eager to adopt and implement simplistic standardisation schemes, which are frequently unrelated to safety concerns [2]. Furthermore, while there are several computerised systems for automated stair design, there has been little, if any, interest in computer-based stair design analysis. House stairs is the common thing in the house especially for those who live on doublestorey house. Mostly architectures used exactly the same common house stairs design in every house where ever which country is it. And the disadvantages of house stairs are it can cause stair accidents. Stairs present a potential danger for young children, the elderly, or anyone with mobility issues. And if you ever need to install a stair lift, expect to shell out thousands of dollars. The foldable house stairs can prevent mostly of those accident. This project is made for the purpose of small house with the problem of stairs installation because to build house stair it required a lot of space. This product will help to solve the problem that happened to those people.